Pastoral systems dominated by cereal-fallow combination in North Africa and West Asia - Nefzaoui A.; Ben Salem H. (Dynamics and sustainability of Mediterranean pastoral systems, 1999)
Following a brief description of the traditional pastoral society and the complementarity and-or conflicts between farmers and pastors in North Africa and West Asia region, authors discussed the recent evolution of pastoral system dominated by fallow. They describe the current systems based mainly on rangeland, sedentary small holders mixed farming, and the more recent sedentary intensive system. Most of these systems are located in low rainfall areas of the WANA region and are facing dramatic feed shortage and drought management risks. Rangeland contribution to small ruminant feed requirements is decreasing and barley cultivation is invading the best rangelands, and steppe zones. Therefore, desertification, lost of soil and natural resources is of first concern for the region. Stubble play a key in filling the summer feeding gap. Crop residues from cereals and olive tree are playing more and more important role in almost all the countries. The current systems may be improved through the implementation of some technologies such as (i) the promotion of alternative feed resources, (ii) the fallow replacement with adapted (native) legumes, (iii) the promotion of on-farm shrubs planting and their integration with cereal crops production (alley-cropping). Some examples of complementarity between conventional feeds and shrubs are discussed and illustrate the real potential of such integration.
9. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 1997/11/26-29, Badajoz (Spain)